A Greener and Facile Synthesis of Imidazole and Dihydropyrimidine Derivatives under Solvent‐Free Condition Using Nature‐Derived Catalyst. Issue 26 (12th September 2017) - Tamuli, Kashyap Jyoti; Dutta, Deepjyoti; Nath, Shyamalendu; Bordoloi, Manobjyoti
Abstract: Natural substances are increasingly used now‐a‐days in organic syntheses for their safety aspects towards the environment. We have identified a natural substance which can promote organic reaction and can be sustainable as it can be obtained from plant sources. The natural substance can promote the synthesis of imidazole and dihydropyrimidine derivatives under solvent‐free condition. The method is economical, greener, metal and solvent free for the synthesis of highly functionalized imidazole and dihydropyrimidine derivatives and was promoted by water extract of pomelo (WEP) at room temperature. These WEP promoted reactions are found to afford high yield for the desired products and can be an alternative protocol for the existing procedures. Abstract : In this communication, natural feedstocks are used as an acid promoter for the synthesis of two nitrogen containing adducts. This method leads to formation of imidazole and dihydropyrimidine derivatives under solvent free condition at room temperature. The method is very eco‐friendly, highly efficient, cheap and environmentally benign with excellent productivity up to 99 % within 6 h. This type of acid promoter can also provide an alternative way to the existing processes.